Democracy and human rights - Beetham, David. (Polity Press, 1999)
Defining and Justifying Democracy. Liberal Democracy and the Limits of Democratization. Market Economy and Democratic Polity. Conditions for Democratic Consolidation. Human Rights and Democracy: a Multi-faceted relationship. What future for Economic and Social rights? Human rights as a Model for Cosmopolitan Democracy. Key principles and indices for a Democratic Audit. Democratic Criteria for Electoral systems.